QOL-16. ASSOCIATIONS BETWEEN SENSORY, PERCEPTUAL, AND COGNITIVE IMPAIRMENT IN THE VISUAL DOMAIN IN CHILDREN TREATED FOR OPTIC PATHWAY GLIOMA. Issue 2 (22nd June 2018) - Papini, Chiara; Pitchford, Nicola; Dineen, Rob; Walker, David
Abstract: Paediatric optic pathway glioma (OPG) and its treatment often result in some degree of sight loss, ranging from mild deterioration to total blindness, in one or both eyes. Residual sight has been widely described through key ophthalmological measures (visual acuity, visual fields, and colour vision), but little is known about more complex processes that receive visual input. In this study, we used the three-level model of receptive processes by Hammill et al., (1993) to examine the associations between three levels of visual information processing: 1) sensation, measured through ophthalmological index of visual acuity (VA), 2) perception, assessed through the motor-reduced perception and visual-motor integration indices of the Developmental Test of Visual Perception (DTVP-2/DTVP-A) and 3) cognition, evaluated through the perceptual reasoning and processing speed IQ indices of the Wechsler scale (WISC-IV). Twelve OPG survivors (7 boys, 5 girls), aged between 6 and 13 years, were assessed on these measures. Results showed no significant correlations between VA in the best eye and the other behavioural measures, although all correlations were in the predicted direction. Strong associations were found between the two measures of perception and the two measures of cognition. Across perception and cognition, positive correlations were found, but the only significant association was between visual-motor integration and processing speed. Overall, these results show moderate to strong associations between sensation, perception and cognition within the visual domain for paediatric OPG patients, highlighting the need for clinical assessment at multiple levels of information processing. Further investigation is warranted with a larger sample.